Inpatients Nutritional Requirements Indicator at Army Hospital Dr. Soepraoen Malang - Kumboyono Kumboyono; Vina Vina (Jurnal Ners, 2013)
Introduction: Patient acceptance to diet in fl uences patient intake during the hospitalization. Patient acceptance on meals provided by the hospital can be seen from the left over. Whilst factors which in fl uences patient motivation to finish their meals including addtional food, taste, and adaptation level to the hospital, the aim of this research was to identify factors that related to patient acceptance on meals provided by the hospital in class three ward dr. Soepraoen Hospital, Malang.Method: Descriptive analitic was used as research design with cross-sectional approach. As many as 51 samples were chosen with purposive sampling. Data was analyzed with chi square with 95%signi fi cance.Results: The results showed a signi fi cant relation between additional food and the leftover (p-Value = 0,018). There is signi fi cant relation on the taste and the leftover (p-Value = 0.032) and adaptation level and leftover (p-Value = 0.026).Discussion: It can be concluded that additional food, taste, and adaptation level to the hospital have signi fi cant relation with hospitalized patient acceptance on their diet. It is suggested that nurse pay more attention on these factors to fulfi ll patient nutrition needs during hospitalization.